Potassium fertilization in flooded rice according to soil cation exchange capacity - Anghinoni, Ibanor; Carmona, Felipe de Campos; Genro Junior, Silvio Aymone; Boeni, Madalena (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the response of flooded rice to the application of potassium doses, according to the soil cation exchange capacity (CEC). Sixteen soils with different CEC at pH 7.0 (CTCpH7), divided in two classes, were used: soils with CTCpH7 up to 15 cmolc dm-3 and CTCpH7 higher than this value. The experiment was carried out in the crop seasons of 2005/2006 and 2006/2007, in eight places per crop year, using different rice cultivars, according to the place or year. The average increment in rice production due to the applied doses of K was calculated, according to the K/CTCpH7 ratio. The potassium maximum economic efficiency dose (MEED) was calculated according to the prices of the fertilizer and rice, practiced from 2003 to 2012. Rice responded economically to potassium fertilization, in both soil CTCpH7 classes used, with higher increase in productivity in soils with lower K/CTCpH7 ratio. In the ten-year average, the DMEE was always greater than U$ 100.00 and higher in soils with CTCpH7>15.0 cmolc dm-3.
Keywords: Oryza sativa; calibration; economic efficiency; fertilizer recommendation; CEC saturation